The Correlation and Regression Analysis of The Growth and Physiological Parameters: How Paclobutrazol Increases Bulb Yield on Three Cultivars of True Shallot Seed - Elizani, Prahesti; Sulistyaningsih, Endang (Universitas Sebelas Maret, 2019)
True Shallot Seed (TSS) is a planting material for shallots in the forms of seeds. It shows a visual appearance of the fresh green shoot even though in the harvest season. This condition indicates that TSS still has potential assimilates which should be optimized for bulbs formation. Paclobutrazol is increasing assimilate translocation from source to sink by activating the sucrose transporter enzyme and changing the phytohormones balance. The study aimed to find out how paclobutrazol increased bulb yield on TSS by analyzing the closeness in the relationship between and the influence of physiological property variables and growth analysis. The study was conducted at Gadjah Mada University experimental field, Yogyakarta, from September to November 2017. It was arranged in a Randomized Complete Block Design with three replications. The first factor included the paclobutrazol concentration (0, 15, 30 and 45 mg L-1), while the second one included TSS cultivars (Tuk Tuk, Sanren and Lokananta). Correlation and regression were used in the data analysis. The results revealed that paclobutrazol significantly affected the physiological properties and the growth of TSS, instead of cultivars. Regression analysis showed that the effect of the concentration of the applied paclobutrazol formed quadratic pattern, where most observed variables had a positive correlation with shallot productivity. Paclobutrazol increased bulb yield by maintaining shoot biomass duration (SBD) and chlorophyll content which had a positive and linear effect on plant growth rate (PGR). The PGR might increase bulb yield per planting hole and indirectly increase its productivity. Paclobutrazol application at 15-30 mg L-1 could be used to improve bulb yield in TSS.